PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS PENEMUAN TERBIMBING PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN KELAS XI SMA. - Abdurrahman Abdurrahman; Gardjito Gardjito; Retni Sulistyoning Budiarti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2015)
ABSTRACT Research and development are aimed at developing the student's Activity sheet-based discovery learning in the activity of learning the material tissue structure and function in plants grade XI high school. The development model used was ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation). The subject of the test is 10 students of Class XI IPA InsanCendekia Islamic Senior High School Jambi. The data type on the data of the research was the qualitative and quantitative data. Research on data collection instrument a question form (questionnaire). Data analysis technique used is qualitative data analysis and quantitative data analysis using the rating scale choice response scale of four. The results of the development of products that have already developed validated by media expert with percentage 76,25% by category very well done one time revision and worksheets students deserve tested by appropriate revision suggestions. While the results of the validation material experts retrieved the percentage of 85% category 2 times with very good revision and worksheets students deserve tested by appropriate revision suggestions. Furthermore, the results of tests obtained by the percentage of the small group of 83.25% belong to the category of very good. Based on these results it can be concluded that the product of the student worksheet-based discovery of social interactions, developed very decent used in biology learning activities in schools or learning independently. Keyword: student’s activity sheet, discovery